Is Incidence of Hysterectomy Increased in Post Tubal Ligated Patients due to Dysfunctional Uterine Bleeding? - Iram Munawar, Nadia Zahid, Amna Aslam (Journal of Rawalpindi Medical College, 2015)
Background: To determine if previous bilateral tubal ligation (BTL) increases the risk of hysterectomy due to dysfunctional uterine bleeding (DUB). Methods: In this case-control study female patients with bilateral tubal ligation, undergoing hysterectomy due to abnormal uterine bleeding were included. These patients were divided into two groups. Group A (study group) were those who had undergone BTL in past and group B (control group) were those not having history of tubal ligation. Hysterectomy was done in all these patients and demographic data including age, hemoglobin (Hb) level and parity were recorded. The incidence of hysterectomy in patients with DUB was compared in both groups. Frequencies and percentages were calculated for qualitative variables like number of patients undergoing hysterectomy in both groups using chi-square test. The Odd’s Risk (OR) and its 95% Confidence Interval (CI) was calculated and p-value ≤ 0.05 was considered as significant. Results: A total of 313 patients underwent hysterectomy during this period. Among them, 89 patients were operated due to DUB. Of these 89 patients, 28 (31.4%) had history of BTL (Case group) while 61 (68.5) had no history of BTL (Control group). These groups were comparable to each other in terms of age, parity and Hemoglobin levels. Also statistical analysis showed that there was no association between BTL and hysterectomy due to DUB (OR=0.623; 95% CI: 0.41- 0.93) Conclusion: Bilateral tubal ligation is not a risk factor for future hysterectomy in patients with history of bleeding of endometrial origin.